2019
DOI: 10.1021/acs.biochem.9b00772
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dynactin in the Intracellular Localization and Activation of Cytoplasmic Dynein

Abstract: Cytoplasmic dynein, the major minus end-directed motor protein in several cell types, transports a variety of intracellular cargo upon forming a processive tripartite complex with its activator dynactin and cargo adaptors such as Hook3 and BicD2. Our current understanding of dynein regulation stems from a combination of in vivo studies of cargo movement upon perturbation of dynein activity, in vitro single-molecule experiments, and cryo-electron microscopy studies of dynein structure and its interaction with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…Dynactin localizes at multiple sites in the cell, including MTs, the mitotic spindle, centrosome, nuclear envelope, GA, kinetochores, and the cell cortex (Tirumala & Ananthanarayanan, 2020). In HeLa cells infected with L2+pDre1 FLAG , endogenous p150 glued and Dre1 colocalize at the inclusion membrane (Figure S1D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynactin localizes at multiple sites in the cell, including MTs, the mitotic spindle, centrosome, nuclear envelope, GA, kinetochores, and the cell cortex (Tirumala & Ananthanarayanan, 2020). In HeLa cells infected with L2+pDre1 FLAG , endogenous p150 glued and Dre1 colocalize at the inclusion membrane (Figure S1D).…”
Section: Resultsmentioning
confidence: 99%
“…Dynactin localizes to multiple compartments and structures in cells where it organizes MTs, facilitates vesicle trafficking, and positions organelles, suggesting that there may be functionally distinct sub-populations of dynactin (Schroer & Verma, 2021;Tirumala & Ananthanarayanan, 2020). Since C. trachomatis inclusions associate with centrosomes and the MTOC (Grieshaber et al, 2003(Grieshaber et al, , 2006Hackstadt et al, 1999), we were particularly interested in the population of dynactin that localizes at the centrosome, where it anchors MTs and organizes MT arrays during interphase and mitosis (Askham et al, 2002;Quintyne et al, 1999;Quintyne & Schroer, 2002).…”
Section: Dynactin Binding Domain Targets Dre1 To the Centrosomal Mtocmentioning
confidence: 99%
“…How dynactin assists dynein is a long-standing controversy (2,5,6,12). Here we quantified the ability of native dynein-dynactin teams to generate force after perturbing the dynein-dynactin and dynactin-MT interactions on phagosomes and SLBs.…”
Section: Discussionmentioning
confidence: 99%
“…Additional interactions between dynein heavy chain and dynactin's Arp domain may stabilize the complex (3,4). How all these linkages help dynein-dynactin to function is hotly debated (5,6). Of particular interest is the recruitment of dynein-dynactin to cargoes by different adaptor proteins (1), as also revealed by the cryogenic electron microscopy (cryo-EM) structure of dynein-dynactinadaptor complexes wherein two dimeric dynein motors were found to be recruited as a pair (3,4).…”
mentioning
confidence: 99%
“…MT plus ends thus decorated with dynactin also accumulated dynein at these sites, and evidence suggested that cargo transport was initiated when these MT plus ends contacted intracellular cargo (Vaughan et al , 2002; Moughamian et al , 2013). However, MT plus end-mediated initiation of dynein-driven transport appears to vary with cell type and context (Watson & Stephens, 2006; Kim et al , 2007; Tirumala & Ananthanarayanan, 2020). Therefore, using SD microscopy in combination with super-resolution radial fluctuations (SRRF, (Gustafsson et al , 2016)) we first quantified the localisation of p150 (Fig.…”
Section: Resultsmentioning
confidence: 99%